20.7k views
3 votes
Pls answer the question!

Pls answer the question!-example-1
User Khex
by
5.1k points

2 Answers

3 votes

Answer:

D)

Step-by-step explanation:

First, let's rearrange the first equation in order to use the substitution method:

3x - y = 12

Add y to each side:

3x = 12 + y

Subtract 12 from both sides:

3x - 12 = y

y = 3x - 12

Then use substitution to solve for y:


(8^x)/(2^y)


(8^x)/(2^(3x-12))

From my perspective, this is the farthest you can get until you can solve, so there is not enough information to solve this.

User Jacques Koekemoer
by
4.2k points
3 votes

Answer:(3x-12)

Step-by-step explanation:Rearranging the equation we get,

3x-12=y

which equals to

1/y=1/(3x-12)

Now,multiply both sides by x

x/y=x/(3x-12)

8x/2y=4x/y=4x/(3x-12)

User Axel Richter
by
4.8k points